Mechanical properties of mesh materials used for hernia repair and soft tissue augmentation - Pott, Peter Paul; Schwarz, Markus; Gundling, Ralf; Nowak, Kai; Hohenberger, Peter; Rößner, Eric (PLOS ONE, 2012)
Background: Hernia repair is the most common surgical procedure in the world. Augmentation with synthetic meshes has gained importance in recent decades. Most of the published work about hernia meshes focuses on the surgical technique, outcome in terms of mortality and morbidity and the recurrence rate. Appropriate biomechanical and engineering terminology is frequently absent. Meshes are under continuous development but there is little knowledge in the public domain about their mechanical properties. In the presented experimental study we investigated the mechanical properties of several widely available meshes according to German Industrial Standards (DIN ISO). Methodology/Principal Findings Six different meshes were assessed considering longitudinal and transverse direction in a uni-axial tensile test. Based on the force/displacement curve, the maximum force, breaking strain, and stiffness were computed. According to the maximum force the values were assigned to the groups weak and strong to determine a base for comparison. We discovered differences in the maximum force (11.1±6.4 to 100.9±9.4 N/cm), stiffness (0.3±0.1 to 4.6±0.5 N/mm), and breaking strain (150±6% to 340±20%) considering the direction of tension. Conclusions/Significance The measured stiffness and breaking strength vary widely among available mesh materials for hernia repair, and most of the materials show significant anisotropy in their mechanical behavior. Considering the forces present in the abdominal wall, our results suggest that some meshes should be implanted in an appropriate orientation, and that information regarding the directionality of their mechanical properties should be provided by the manufacturers.